"Should Patients With Substance Use Disorders Be Prescribed Benzodiazepines?" No. Issue 2 (March 2017) - DuPont, Robert L.
Abstract : Patients with substance use disorders (SUDs) should not use benzodiazepines to treat anxiety, insomnia, or anything else, for the same reasons that they should not drink any alcohol or use other drugs, regardless of their primary drug used. Once the addiction "switch" is thrown on, it never again goes off. This question has additional relevance today because in 2016, the US Food and Drug Administration put black box warnings on all benzodiazepines and opioid analgesics about the serious risks associated with their concomitant use. Anxiety is not a benzodiazepine-deficiency disease. It is possible to treat anxiety and insomnia without medicines of any kind, and it is possible to use medicines other than benzodiazepines for these common and serious mental disorders. Although many patients with SUDs are eager to use benzodiazepines, using alternatives is often effective and it does not put the patient's recovery in jeopardy. The standard I propose here is based on the experience of many people with SUDs who have tried and failed to use benzodiazepines for anxiety.